A selectable, plasmid-based system to generate CRISPR/Cas9 gene edited and knock-in mosquito cell lines - Kathryn Rozen-Gagnon (Nature Portfolio, 2021)
Abstract Aedes (Ae.) aegypti and Ae. albopictus mosquitoes transmit arthropod-borne diseases around the globe, causing ~ 700,000 deaths each year. Genetic mutants are valuable tools to interrogate both fundamental vector biology and mosquito host factors important for viral infection. However, very few genetic mutants have been described in mosquitoes in comparison to model organisms. The relative ease of applying CRISPR/Cas9-based gene editing has transformed genome engineering and has rapidly increased the number of available gene mutants in mosquitoes. Yet, in vivo studies may not be practical for screening large sets of mutants or possible for laboratories that lack insectaries. Thus, it would be useful to adapt CRISPR/Cas9 systems to common mosquito cell lines. In this study, we generated and characterized a mosquito optimized, plasmid-based CRISPR/Cas9 system for use in U4.4 (Ae. albopictus) and Aag2 (Ae. aegypti) cell lines. We demonstrated highly efficient editing of the AGO1 locus and isolated U4.4 and Aag2 cell lines with reduced AGO1 expression. Further, we used homology-directed repair to establish knock-in Aag2 cell lines with a 3xFLAG-tag at the N-terminus of endogenous AGO1. These experimentally verified plasmids are versatile, cost-effective, and efficiently edit immune competent mosquito cell lines that are widely used in arbovirus studies.